Self-reported symptom burden among patients attending public health care facilities in India: Looking through ICPC-3 lens. - Priti Gupta; Bhavna Bharati; Kirti Sundar Sahu; Pranab Mahapatra; Sanghamitra Pati (Public Library of Science (PLoS), 2024)
Introduction The objectives of this study were: 1) to describe the socio-demographics and classify the chief complaints and reasons to encounter facilities of patients presenting to public healthcare facilities; 2) to explore differences in these complaints and: International Classification of Primary Care-3 (ICPC-3) groups across socio-demographic and health system levels. Methods This is a cross-sectional study conducted in three districts of Odisha, India. Within each district, the district hospital (DH), one Sub-district hospital (SDH) (if available), two Community health centers (CHCs), and two Primary health care centers (PHCs) were selected. Thus, a total of three DHs, three SDHs, six CHCs, and six PHCs were covered. Two tertiary healthcare facilities were also included. Patients aged 18 years and older, attending the Outpatient Departments (OPD) of sampled health facilities were chosen as study participants through systematic random sampling. Results A total of 3044 patients were interviewed. In general, 65% of the sample reported symptoms as their chief complaint for reason of encounter, whereas 35% reported disease and diagnosis. The most common reasons to encounter health facilities were fever, hypertension, abdominal pain, chest pain, arthritis, skin disease, cough, diabetes, and injury. Among the symptoms, the highest number of patients reported the general category (29%), followed by the digestive system (16%). In the disease category, the circulatory system has the highest proportion, followed by the musculatory system. In symptom categories, general, digestive, and musculatory systems were the key systems for the reasons of encounter in outpatient departments irrespective of different groups of the population. In terms of different tiers of health systems, the top three reasons to visit OPD were dominated by the circulatory system, respiratory system, and musculatory system. Conclusion This is the first Indian study using the ICPC-3 classification for all three levels of health care. Irrespective of age, socio-economic variables, and tiers of healthcare, the top three groups to visit public health facilities according to the ICPC-3 classification were consistent i.e., general, digestive, and circulatory. Implementation of standard management and referral guidelines for common diseases under these groups will improve the quality and burden at public health facilities in India.